Perlindungan Hukum dan Kebijakan Tarif Pajak Terhadap Trader Crypto di Indonesia - Syah Budianto Chai Putra, Reinan (UM Purwokerto Press, 2024)
Cryptocurrency investment in Indonesia has become an increasingly popular topic as people's interest in digital assets increases. Although there is potential for huge profits, there are also risks that need to be considered. The Indonesian government takes a cautious stance in regulating cryptocurrencies. Clear regulations still do not exist, although in 2019, the Commodity Futures Trading Supervisory Agency (BAPPEBTI) issued regulations recognizing cryptocurrencies as commodity futures that can be traded on futures exchanges. Bank Indonesia has issued a statement reminding the public of the risks associated with the use of digital currencies, but there has been no outright ban on their use. There are also concerns regarding the misuse of cryptocurrencies for illegal purposes, such as money laundering and terrorism financing, which are continuously monitored by governments and financial regulatory agencies. Despite regulatory uncertainty, interest in cryptocurrencies continues to grow in Indonesia, and more and more companies and individuals are interested in understanding and using this technology.